The ideological structure of the Islamic Republic of Iran: Study in the theory of the Wilayat alfaqih - دکجۆر ئٍویي فٍرەج شٍریف; واوۆسجاى یاریدەدەر ًیشجىان ڕەشید عٍمی (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The basic idea of this study entitled: ( The political system of the Islamic Republic of Iran: a study of the implications of Wellyat Al-Faqih ) is to highlight on the study and analysis of the Iranian political system (methodological study), focusing on the issue of Wellyat Al-Faqih, which represents the Iranian Islamic state ideology. This ideology which has played a central orientation role and ongoing since the triumph of the revolution of the Iranian people against the monarchy in Iran in 1979 till now, which is the same (the theory of Wellyat Al-Faqih) that have been came an identification with the construction formulations of the constitutional Iranian political system and its characteristics, under the influence of ideas and directions of Imam Khomeini, in which the Supreme Guide of Islamic Revolution (Wellyat Al-Faqih) Considered the high authority in political and religion affairs inside the political system of Iran. Methodological, adopted in our study the entrance to the political Ideology in the context of the case study approach, by focusing on the role of religious- political culture of the (the 12th Imamy Shiite) in general, as an impotence which gives legitimacy to various political systems, by focusing on principle of " Wellyat Al-Faqih " in the Iranian Current political system, as the most important elements in the Iranian contemporary Political Culture. We divide our study into three topics, in the first topic we discussed the case of the historical context of the emergence of the theory of Wellyat Al-Faqih, to deal with the theoretical level of the problematic of the relation between the religion authority in the Shi'ite political thought (Al-Imamy), thus, through standing in most important outstanding stages of the theory Since the beginning centuries of Hegira until the era of The Safavid State. In the second topic we have shed light on the question of the development of the Wellyat Al-Faqih from idea to theory of power, Through which we referred to the experience of the Safavid state and the additions and developments that took place on the theory of the Wellyat AlFaqih in the stages that followed the Safavid state, Especially Khomeini's attempts in this regard But, in the third and final topic we have focused on embodiments of the theory of Wellyat Al-Faqih in the Iranian political system, which came as practical application of the views of Khomeini directions in this regard. In the end of the study we mentioned the most important conclusions that we reached